F: Comprehensive Periodic Health Check-Ups for Community Health Center Workers as Fulfillment of Health Rights - Nitro - Galenso; Sukmawati Sukmawati; Abdullah Abdullah; Nur Ambiya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Regular health check-ups (Medical Check-Ups/MCUs) are critical for human resources (HR) at Public Health Centers (Puskesmas), which include medical personnel, health workers, and health support staff, as well as the health care facilities where they work. Thus, regular employee health checks are essential to fulfil every citizen's right to health, enabling them to work optimally in optimal health condition. The purpose of this study is to gather information about health workers' perspectives on fulfilling their health rights while working, as well as the barriers to implementing periodic health checks on health workers at Community Health Centers. Subjects and Method: This is an observational study with a descriptive qualitative design which was carried out at community health centers in Banggai Regency from May to October 2025. This study's population included health workers representing their professions at each community health center, the overall number of research participants was 75 health workers. Thematic analysis will be used to describe the findings from in- depth interviews. While primary data on the implementation and impediments to frequent health check-ups, gathered by a questionnaire. Results: From 13 questions regarding the health workers perspective about comprehensive regular check-up, 11 of them are agreed and strongly agreed by the majority of respondents(>80%). The majority of repondents also disagreed and strongly disagreed when asked whether the comprehensive regular check-up is only for those who are already sick or only for those who are more than 40 years old. Conclusion: The majority of respondents are aware of their right to regular health check- ups, indicating that healthcare workers are extremely concerned about their health while working owing to occupational risks.